johnnyV

5 Reputation

2 Badges

12 years, 151 days

MaplePrimes Activity


These are questions asked by johnnyV

Hi,

I'm searching for the third differential equation that will transform the following two equations non-autonomous system into a three equations autonomous one:

diff(x(t),t)=-x(t)+2*(m*t+n)*y(t)-2*k*(m*t+n)2

diff(y(t),t)=-y(t)+k*m-(m*t+n)*((x(t)/2)-1)

 

diff(z(t),t)= ...

 

Regards,

Johnny

Hello,

I'm trying to solve the following system in Maple but it doesn't show me any solution:

2*(1-a1^2)*x(t)*y2(t) - 2*k*(1-a1*a2)*(x(t)^2)=m

k*diff(x(t),t)-diff(y2(t),t)=x(t)(m/2-1)+y2(t)

where x(0)=0 and y2(0)=0 , k>0,...

Page 1 of 1